(untitled) (Fiep Bulletin - online, 2014)
Evidences show that the growth’s impetus in adolescence may predispose children to injuries (MICHELI And MINTZER, 2002). The goal of this work is to suggest a program of Preventive Physiotherapy considering the relationship between injuries and postural changes existing in each sport category. This is a transversal study field, based in a bibliographical survey. Using a questionnaire adapted from Baptista et al (1999) as a tool, it was also held a Physiotherapeutic evaluation. The data was collected and organized in a spreadsheet from Excel 2007. After this analysis data compatible scientific evidences was searched, providing subsidies for the development of a Program of Preventive Physiotherapy. 176 athletes were evaluated, being men: 43 of indoor soccer, 15 of basketball and 73 football; And women: 12 of indoor soccer, 12 of basketball and 21 of volleyball. The postural profile presented by male athletes was: lateral deviation, cervical hyperlordosis, thoracic hypercifosis, lumbar hyperlordosis, knee aligned with hyperextension tendency, knee varus in futsal, valgus in football and basketball, ankle aligned with the trend to valgus, foot plan with aligned tendency. And the women: lateral deviation, normal cervical lordosis, thoracic hypercifosis, lumbar hyperlordosis, knee aligned with valgus tendency and hyperextend, ankle aligned with valgus tendency, foot plan. Places of lesions in males: indoor soccer, knee; Football, lumbar spine and knee and basketball, knee. Female: basketball, ankle; Volleyball, knee and indoor soccer, knee. It is suggested that the Programs of sportive Physiotherapy evidence the preservation with postural reeducation classes aiming at the articular rebalance, the agonist/antagonist relationship and proprioception to prevent injuries and improve the neural muscle responses. Already the kinetic therapy in the water may be used respecting the periodization of training after competition. This program is being done in FAEFIJA, in agreement with the Department of Municipal Sports.